Effect of short inter-pregnancy interval on perinatal outcomes among pregnant women in North-west Ethiopia: A prospective cohort study - Gurmu, Leta; Wakgari, Negash; Kolola, Tufa; Danusa, Kababa Temesgen (Frontiers in Public Health, 2022)
Background: Inter-pregnancy interval (IPI) is the elapse of time between the end of one pregnancy and the conception of another pregnancy, while birth to pregnancy interval, is the time gap between live birth and the conception of the next pregnancy. Hence, this study assessed the effects of short inter-pregnancy intervals on perinatal outcomes among women who gave birth in public health institutions of Assosa zone, North-west Ethiopia. Methods: An institution-based prospective cohort study was conducted among 456 mothers who visited health facilities for the fourth antenatal care appointment (152 exposed and 304 non-exposed). Women who gave their recent birth with a pregnancy interval of <24 months or/and had an abortion history of <6 months were considered as exposed otherwise non-exposed. Data was collected through face-to-face interviews by using questionnaires and checklists. The collected data was entered using Epi-data and exported to STATA for analysis. A log-binomial regression model was used to identify the effect of short inter-pregnancy intervals on the perinatal outcomes. Results: The overall incidence of adverse perinatal outcomes is 24%. Mothers who had short inter-pregnancy intervals have two times the risk to develop low birth weight (RR: 2.1, 95%CI: 1.16-3.82), and low Apgar score (RR: 2.1, 95%CI: 1.06-2.69). Similarly, the risk to develop small for gestational age (RR: 2.6, 95% CI: 1.19-7.54), and preterm birth (RR: 3.14, 95%CI: 1.05-4.66) was about 3 times among mothers who had short inter-pregnancy interval compared to mothers who had an optimal inter-pregnancy interval. Conclusion: short inter-pregnancy interval increases the risk of low birth weight, preterm birth, small for gestational age, and low Apgar score. Health Policymakers, National health managers, and health care providers should work on increasing the awareness of optimal inter-pregnancy intervals and postpartum family planning utilization to reduce the effect of short inter-pregnancy intervals on adverse perinatal outcomes.